Basics of granulating feed and excrements - Komar, Artem; Комар, Артем Станіславович; Комар, Артем Станиславович (My University, 2021)
Now in Ukraine there is a clear tendency towards the use of granulators or even whole lines of granulation of feed and waste of various origins. For the production of high-quality granules, you need not only to have a workable technique, but also to know the basics of raw material granulation.
Keywords: granulators; waste; granulating feed